Bioavailability and bioaccessibility of polycyclic aromatic hydrocarbons from (post-pyrolytically treated) biochars. (May 2017) - Hilber, Isabel; Mayer, Philipp; Gouliarmou, Varvara; Hale, Sarah E.; Cornelissen, Gerard; Schmidt, Hans-Peter; Bucheli, Thomas D.
Abstract: Bioaccessibility data of PAHs from biochar produced under real world conditions is scarce and the influence of feedstock and various post-pyrolysis treatments common in agriculture, such as co-composting or lacto-fermentation to produce silage fodder, on their bioavailability and bioaccessibility has hardly been studied. The total (Ctotal ), and freely dissolved (i.e., bioavailable) concentrations (Cfree ) of the sum of 16 US EPA PAHs of 43 biochar samples produced and treated in such ways ranged from 0.4 to almost 2000 mg/kg, and from 12 to 81 ng/L, respectively, which resulted in very high biochar-water partition coefficients (4.2 ≤ log KD  ≤ 8.8 L/kg) for individual PAHs. Thirty three samples were incubated in contaminant traps that combined a diffusive carrier and a sorptive sink. Incubations yielded samples only containing desorption-resistant PAHs (Cres ). The desorption resistant PAH fraction was dominant, since only eight out of 33 biochar samples showed statistically significant bioaccessible fractions (fbioaccessible  = 1 - Cres /Ctotal ). Bioavailability correlated positively with Ctotal /surface area. Other relationships of bioavailability and –accessibility with the investigated post-pyrolysis processes or elemental composition could not be found. PAH exposure was very limited (low Cfree, high Cres ) for all samples with low to moderate Ctotal, whereas higher exposure was determined in some biochars with Ctotal  > 10 mg/kg. Graphical abstract: Highlights: Desorption resistance of PAHs in biochar was determined with contaminant traps. PAHs in biochar were mostly desorption resistant. Where observed, bioaccessibility of PAHs in biochar was concentration independent. Exposure of PAHs in biochar becomes relevant at high concentrations (>10 mg/kgdw ). Biochars acted more as a sink than a source for PAHs.